Factors Associated with the Development, Progression, and Outcome of Dupuytren Disease Treatment: A Systematic Review. (29th November 2021) - Geoghegan, Luke; Man, Julian; Jain, Abhilash; Price, Andrew; Gibbons, Elizabeth; Jerosch-Herold, Christina; Sidey-Gibbons, Chris; Rodrigues, Jeremy N.
Abstract : Background: The factors typically considered to be associated with Dupuytren disease have been described, such as those in the "Dupuytren diathesis." However, the quality of studies describing them has not been appraised. This systematic review aimed to analyze the evidence for all factors investigated for potential association with the development, progression, outcome of treatment, or recurrence of Dupuytren disease. Methods: A systematic review of the Cochrane Central Register of Controlled Trials, MEDLINE, Embase, and Cumulative Index to Nursing and Allied Health Literature databases was conducted using a Preferred Reporting Items for Systematic Reviews and Meta-Analyses–compliant methodology up to September of 2019. Articles were screened in duplicate. Prognostic studies were quality assessed using the Quality in Prognosis Study tool. Results: This study identified 2301 records; 51 met full inclusion criteria reporting data related to 54, 491 patients with Dupuytren disease. In total, 46 candidate factors associated with the development of Dupuytren disease were identified. There was inconsistent evidence between the association of Dupuytren disease and the presence of "classic" diathesis factors. The quality of included studies varied, and the generalizability of studies was low. There was little evidence describing the factors associated with functional outcome. Conclusions: This systematic review challenges conventional notions of diathesis factors. Traditional diathesis factors are associated with disease development and recurrence, although they are not significantly associated with poor outcome following intervention based on the current evidence.